Radiographic evaluation of the effect of endotoxin (LPS) plus calcium hydroxide on apical and periapical tissues of dogs - Nelson-Filho, Paulo; Leonardo, Mario Roberto; Silva, Léa Assed Bezerra; Assed, Sada (Wolters Kluwer, 2002)
The aim of this study was the radiographic evaluation of the apical and periapical region of dog teeth submitted to intracanal bacterial endotoxin (lipopolysaccharide, LPS), associated or not with calcium hydroxide. After removal of the pulp, 60 premolars were divided into four groups and were filled with bacterial endotoxin (group 1), bacterial endotoxin plus calcium hydroxide (group 2), saline solution (group 3), or periapical lesions were induced with no treatment (group 4), for a period of 30 days. Similar periapical lesions were observed in groups 1 and 4. The lamina dura was intact in groups 2 and 3. Bacterial endotoxin (LPS) caused radiographically visible periapical lesions, but when associated with calcium hydroxide, this endotoxin was detoxified. Copyright © 2002 by The American Association of Endodontists.